Seeding Rate for Dryland Wheat - A. Schlegel; J. Holman; L. Haag (Kansas Agricultural Experiment Station Research Reports, 2019)
Four winter wheat varieties (PlainsGold Byrd, Limagrain T158, Syngenta TAM 111, and WestBred Winterhawk) were planted at five seeding rates (30, 45, 60, 75, and 90 lb/a) in the fall of 2014, 2015, 2016, and 2017 at Colby, Garden City, and Tribune, KS. The objective of the study is to identify appropriate seeding rates for dryland winter wheat in western Kansas. Averaged across varieties, a seeding rate of 60 lb/a seemed to be adequate at all locations in 2015. However, with higher yields in 2016, a higher seeding rate (75 lb/a) was beneficial. Although yields were less in 2017 than 2016, a seeding rate of 75 lb/a generally produced the highest yields. In 2018, yield increased with increased seeding rate. The wheat variety T158 was the highest yielding (or in the highest group) at all locations in 2015. Other varieties may have been affected by differential response to stripe rust and winter injury resulting in lower yields. In 2016, the highest yielding variety varied by location. TAM 114 was in the highest yielding variety at each location in 2017. In 2018, Winterhawk was the lowest yielding variety. Variety selection and growing season appears to have more effect on wheat yields than seeding rate. A seeding rate of 30 or 45 lb/a, and often 60 lb/a, resulted in lower yields than the 75 or 90 lb/a rate. Yield response to seeding rate, and optimal seeding rate for any site-year was similar across varieties.
Keywords: winter wheat; seeding rate